Adaptive Robust SMC-Based AGC Auxiliary Service Control for ESS-Integrated PV/Wind Station. (7th October 2020) - Su, Xiao-Ling; Zhao, Zheng-Kui; Si, Yang; Guo, Yong-Qing
Abstract : Power source structure has developed significantly because of the increasing share of renewable energy sources (RESs) in the power system. RESs bring inevitable impacts on power system frequency, voltage regulation, and power system stability. The conventional automatic generation control (AGC) loops which relay only on the synchronous generating units cannot meet the requirements of these new circumstances. This paper presents an ESS-integrated PV/wind station topology and its control structure for AGC auxiliary service in order to provide existing RESs the additional functionality of AGC auxiliary service without changing their control strategies conceived for MPPT mode. The shifting operation modes and external disturbances make ESSs in an ESS-integrated PV/wind station inherently nonlinear and time variable. Therefore, an adaptive robust sliding-mode control (ARSMC) system is proposed. The ARSMC colligates the advantages of adaptive control and SMC contains state feedback term, robust control term, and adaptive compensation term. The strictly logical and rigorous proof using Lyapunov stability analysis indicates the ARSMC system is insensitive to parametric uncertainties and external disturbances; meanwhile, it guarantees fast response speed and high control precision. The case studies on NI-PXI platform validate the effectiveness of the proposed approach.